Assessment of the mutagenic potential of Skadar Lake sediments using the Salmonella microsomal assay - Perović, Svetlana; Perović, A.; Erdinger, Lothar; Hollert, H. (Archives of biological sciences, 2013)
Organic extracts of sediments from Skadar Lake (National park and protected RAMSAR site) were investigated for their mutagenic potential using Salmonella typhimurium TA98 and TA100 strains in the presence and absence of metabolic activation. Five different concentrations of sediment extracts from five different sampling sites were assayed, and mutagenic results were obtained for both strains. These studies present a part of the EULIMNOS project and included a battery of bioassay testing and in situ investigations of microbial community structures of Skadar Lake sediments. The obtained results show mutagenic risk potential in five collected samples in the absence and presence of metabolic activation. Additional studies are required in order to identify and quantify the chemical compounds responsible for the mutagenic activity present in Skadar Lake sediments.
Gesehen am 10.01.2022